Propriedades de simetria para soluções de equações elípticas quase lineares em modelos riemannianos - Costa, Ricardo Pinheiro da (2014)
In this work we investigate monotonicity and symmetry properties of of solutions to equations involving the p-Laplace-Beltrami operator in hyperbolic space and sphere. The main tools used to obtain the result is a variant of the method of moving planes and a careful use of the maximum and comparison principles